2020
DOI: 10.1136/jitc-2019-000247
|View full text |Cite
|
Sign up to set email alerts
|

Histiocyte predominant myocarditis resulting from the addition of interferon gamma to cyclophosphamide-based lymphodepletion for adoptive cellular therapy

Abstract: BackgroundAdoptive cellular therapy (ACT) is a promising treatment for synovial sarcoma (SS) with reported response rates of over 50%. However, more work is needed to obtain deeper and more durable responses. SS has a ‘cold’ tumor immune microenvironment with low levels of major histocompatibility complex (MHC) expression and few T-cell infiltrates, which could represent a barrier toward successful treatment with ACT. We previously demonstrated that both MHC expression and T-cell infiltration can be increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Consistent with prior reports, 10 16 transferred cells in all patients predominantly had a memory phenotype ( figure 2A and B ) 17 with very few cells that were double positive for CD39 and CD103. While few cells expressed PD-1, we also tested for Tim-3, an exhaustion marker that also suggests antigen experience ( online supplemental figure 5 ), and there was a non-statistically significant trend toward higher expression on tet+ cells compared with tet− controls (most pronounced in Cy1, figure 2C and D ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with prior reports, 10 16 transferred cells in all patients predominantly had a memory phenotype ( figure 2A and B ) 17 with very few cells that were double positive for CD39 and CD103. While few cells expressed PD-1, we also tested for Tim-3, an exhaustion marker that also suggests antigen experience ( online supplemental figure 5 ), and there was a non-statistically significant trend toward higher expression on tet+ cells compared with tet− controls (most pronounced in Cy1, figure 2C and D ).…”
Section: Resultssupporting
confidence: 92%
“…20 MHC expression and T-cell infiltration into these tumors can be increased by systemic IFNγ 21 ; however, incorporation of cytokines into ACT regimens must be done with great care. 10 Our data suggest that more could be done to support transferred T cells after the time of infusion, possibly using post-infusion IL-15, a cytokine known to support memory T cells. 18 High IL-7 and IL-15 following lymphodepletion may aid responses for some patients, but as levels fall, transferred T cells may fall as well.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, systemic delivery of IFN-γ can be associated with significant toxicity. 32 Studies in animal models have suggested that a primary mode of tumor control by type I T cells is not direct lysis of tumor, but rather the induction of cell cycle arrest by the secretion of IFN-γ. 33 Initiation of cytokine secretion by CD4 T cells after antigen stimulation is an early event.…”
Section: Discussionmentioning
confidence: 99%
“… 91 Based on these results IFNγ was combined with NY-ESO-1 specific T cell therapy in a clinical trial but had a fatal complication. 92 Subsequently, a multicenter trial combining IFNγ with PD-1 inhibition has been completed and data analysis is ongoing (NCT03063632).…”
Section: Ss Microenvironmentmentioning
confidence: 99%